IGFLR1 as a Novel Prognostic Biomarker in Clear Cell Renal Cell Cancer Correlating With Immune Infiltrates - Song, Wenjing; Shao, Youcheng; He, Xin; Gong, Pengju; Yang, Yan; Huang, Sirui; Zeng, Yifan; Wei, Lei; Zhang, Jingwei (Frontiers in Molecular Biosciences, 2020)
Objective: Insulin Growth Factor-Like receptor 1 (IGFLR1) reflects progressive disease and confers a poor prognosis in clear cell renal cell cancer (ccRCC). However, extensive studies highlighting the mechanisms involved in how IGFLR1 triggers the progression of ccRCC remain lacking. Methods: In the present study, the expression level of IGFLR1 mRNA and correlation between IGFLR1 expression and prognosis of ccRCC were analyzed based on The Cancer Genome Atlas (TCGA) ccRCC cohort. Further, we analyzed methylation and copy number variation to try to explain the difference in IGFLR1 expression. Subsequently, we investigated the correlation between IGFLR1 and tumor-infiltrating immune cells with the aid of TIMER (Tumor Immune Estimation Resource). The potential candidates’ genes associated with IGFLR1 were screened by variation analysis, which were used for further enrichment analysis of signaling pathways and immune gene sets to infer the certain function and corresponding mechanisms in which IGFLR1 was involved in ccRCC. Finally, we establish prognostic risk models using multivariate Cox regression analysis and analyzed the possible involvement of IGFLR1 in chemotherapeutic drug resistance. Results: The results showed that upregulated IGFLR1 was detected in ccRCC compared with para-cancer tissues and significantly affected the prognosis of ccRCC (overall survival: Logrank p < 0.0001; disease free survival: Logrank p = 0.022). Univariate and multivariate analyses indicated that IGFLR1 was an independent prognostic factor for ccRCC (HR=2.064, p = 0.006) and the risk prognostic model based on age, M, level of platelet and calcium and IGFLR1 expression had satisfying predictive ability. The correlation analysis showed that the expression level of IGFLR1 was positively correlated with the abundance of myeloid derived suppressor cell and their marker genes in ccRCC significantly. IGFLR1 may be related to the regulatory activation, intercellular adhesion of lymphocytes and drug resistance in cancer. Conclusions: These findings suggested that IGFLR1 was significantly associated with the prognosis in a variety of cancers, particularly ccRCC. IGFLR1 may play an important role in tumor related immune infiltration and showed potential diagnostic, therapeutic and prognostic value in ccRCC.